THE CONSTRUCTION OF THE CONCEPT OF HOME IN THE EXPERIENCES OF HOMELESS PEOPLE - Smiciute, Dovilė; Motiečienė, Roberta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
This paper analyses the construction of the concept of home on the basis of subjective experiences of homeless people. Home as a social construct is revealed by analysing experiences of 5 homeless people. Based on the subjective experiences of homeless people, a qualitative research revealed that safe and private home is one of the main needs of people experiencing homelessness. The construction of home is based on past events and the experience of the reality of the past: the childhood home and created constructs of home, safety and independence as well as certain feelings and emotions. The participants of the research are people experiencing homelessness.